2011
DOI: 10.2174/1874829501104010066
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Land Use Activities on Vegetation Cover and Water Quality in the Lake Victoria Watershed

Abstract: Abstract:The impact of land use activities on loss of vegetation cover and water quality was assessed in three selected sites within the Lake Victoria Basin using remote sensing technologies and standard water quality analysis techniques. The three study sites were: (i) Nzoia River Basin (Kenya), (ii) Nakivubo Wetland (Uganda) and (iii) Simiyu drainage basin (Tanzania). Lake Victoria is the second largest fresh water lake in the world and is served by a drainage basin area of over 193,000 km 2 , traversing fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…The results found in this study are also consistent with that of Twesigye et al (2011) who observed that, built-up was increasing while forestland is decreasing around the Nakivubo wetland which is within the area studied. However, the extent of change differ due to the area of land considered and the classification method used.…”
Section: Discussionsupporting
confidence: 92%
“…The results found in this study are also consistent with that of Twesigye et al (2011) who observed that, built-up was increasing while forestland is decreasing around the Nakivubo wetland which is within the area studied. However, the extent of change differ due to the area of land considered and the classification method used.…”
Section: Discussionsupporting
confidence: 92%
“…The land use characteristics of river watersheds are directly related to downstream lake and reservoir environments, with negative influences being reported in many previous studies (e.g. Beaver et al., ; Fraterrigo & Downing, ; Lizotte et al., ; Nielsen et al., ; Pilgrim, Mikhailova, Post, & Hains, ; Soranno, Cheruvelil, Wagner, Webster, & Bremigan, ; Twesigye, Onywere, Getenga, Mwakalila, & Nakiranda, ). River water chemistry is controlled by numerous natural and anthropogenic factors, including pollutants from point and nonpoint sources (Ahearn et al., ), transported downstream via river channels.…”
Section: Introductionmentioning
confidence: 90%
“…The vitality of the lake has been adversely affected, however, by waste discharges from various activities around the lake (Njiru et al, 2012). The impacts of pollution from agricultural, municipal and industrial discharges, for example, are visible in some of the rivers draining into the lake and along its shoreline, especially at Port Victoria in Busia and Winam Gulf in Kisumu (Twesigye et al, 2011). Cyanobacteria blooms also are currently becoming an increasingly common phenomenon near the shores of Lake Victoria (Lung'ayia, M'Harzi, Tackx, Gichuki, & Symoens, 2000).…”
Section: Study Areamentioning
confidence: 99%